(untitled) (ESMAT Magazine, 2025)
ABSTRACT: Riverside communities in the Amazon have historically been affected by the advance of development and economic growth in Brazil. However, the reality of these communities is still precarious and there is a lack of studies to understand development as it relates to social public policies. In this context, the objective of this research was to carry out a systematic review of CAPES journals in order to discuss what scientific articles published and peer-reviewed say about the category of development (substantial freedoms and social opportunities) and/or designed as conditional income transfer programs as from the year 2018. This was an exploratory study with a qualitative approach using a bibliographical and documental approach. The methodological procedure consisted in the definition by category of analysis, the adoption of operational concepts by topic, and the triangulation for analysis by connecting development as freedom with the operational concepts defined. Conclusions were drawn that conditional income transfer programs hold a significant place in development as freedom in the everyday lives of communities. However, further research is needed to demonstrate the precise impact of social public policies on communities and traditional peoples, particularly in terms of sustainable development and constitutional guarantees.